2020
DOI: 10.15430/jcp.2020.25.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Survival Status and Predictors of Mortality Among Colorectal Cancer Patients in Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia: A Retrospective Follow-up Study

Abstract: Colorectal cancer is one of the commonest cancer types that has a great public health impact both in developed and developing countries. However, in Ethiopia, the survival status of colorectal cancer patients was not well understood. Therefore, the aim of this study was to determine the survival status and predictors of mortality among colorectal cancer patients in Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia in 2019. The institution-based retrospective follow-up study was conducted with 621 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 30 publications
(34 reference statements)
2
22
0
Order By: Relevance
“…Patients diagnosed at stage IV showed a higher rate of death than those diagnosed at stage I or II. This finding is supported by studies from Ethiopia, Taiwan and Ghana, which showed advanced stage at diagnosis is associated with poor survival [17,27,31]. Similarly, a study done in Iran also indicated cancer grade significantly associated with mortality from CRC [39].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Patients diagnosed at stage IV showed a higher rate of death than those diagnosed at stage I or II. This finding is supported by studies from Ethiopia, Taiwan and Ghana, which showed advanced stage at diagnosis is associated with poor survival [17,27,31]. Similarly, a study done in Iran also indicated cancer grade significantly associated with mortality from CRC [39].…”
Section: Discussionsupporting
confidence: 55%
“…In our study, the two-and three-year survival for all stages combined was below 50% and the five-year survival was 28.7%. A study by Atinafu et al reported 21.7% of five-year survival among patients treated in TASH [17]. However, the study has methodological limitations in the event ascertainment and missing data management that could lead to discrepancy in survival estimate.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The three-year survival rates in Ghana were found to be 21% (10), those in Kenya 40% 17 and those in Ethiopia were 47%. 18 These three-year survival rates in Sub-Saharan Africa are lower than those from studies conducted in England (3-year survival for colon carcinoma: 69.5%; 3-year survival for rectal carcinoma: 69.7%), 19 Taiwan (79.4%), 20 Malaysia (55.04%), 21 Kurdistan (57%), 22 Jordan (66%) 23 and Northern Iran (52%). 24 The survival rates of CRC in high-income developed countries such as the United States, parts of Europe, Canada, Australia and New Zealand are better than ours, 1 even though these countries report higher CRC…”
Section: Discussionmentioning
confidence: 80%
“…Recent studies on screening for and following up CRC have mainly adopted insurance database analysis, case review, and questionnaire survey methods [9,19,[21][22][23][24]. Few health authorities have purposefully established a database for people participating in CRC screening containing relevant data from across the whole country.…”
Section: Introductionmentioning
confidence: 99%